The pedagogy of courage: critical Aboriginal football education in Australia's Northern Territory. Issue 3 (27th May 2022) - Knijnik, Jorge; Hunter, Jane
ABSTRACT: This paper discusses key questions of pedagogical hope and courage through non-formal educational activities such as football. We look beyond standard assumptions of sports as a vehicle to stimulate social cohesion and prevent anti-social and criminal behaviour among Aboriginal youth to address core philosophical and pedagogical questions that underpin sporting promotion within underprivileged communities. During the 2014 FIFA World Cup, eight young Aboriginal top-footballers from the town of Borroloola in Australia's Northern Territory, went to the tournament host country, Brazil, to take part in a range of activities, including spending time with local Indigenous communities. This tour was promoted by the John Moriarty Football initiative. Following the tour, the Aboriginal footballers went back to their community to become sporting leaders and also to continue their football careers. With data gathered from interviews with the central participants of the tour, and by using Freire's concepts of emancipation through dialogic practices, hope, critical consciousness, and untested feasibility, we look at the Borroloola youths' football educational activities as a dialogic space where autonomy and citizenship can be enhanced. Employing the Freirean critical dialogue method, the paper unveils the significant connections between non-formal sporting activities and the flourishing of the pedagogy of courage.